EVOLUCION DE LA ACTIVIDAD PROTEOLITICA DEL LATEX MEXICAINA DURANTE EL DESARROLLO DEL FRUTO DEL CUAGUAYOTE PILEUS MEXICANUS - SALAZAR, V; HUERTA, LAURA; HERNANDEZ, A; CASTANEDA AGULLO, M (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1968)
Seeds of Cucurbita argyrosperma, C maxima, C maxima x C moschata, and C pepo extracted with a 10% soln of NaCl showed very similar globulin contents 9-10% Analysis of N, S and amino acids from the globulin crystals are given, but these data do not p
ANAL BIOCHEM
Keywords: EVOLUCION, ACTIVIDAD PROTEOLITICA, LATEX MEXI CAINA , DESARROLLO, FRUTO, CUAGUAYOTE PILEUS MEXICANUS; CIENCIAS DE LA VIDA; MICROBIOLOGIA; PROCESOS MICROBIANOS